Hábitos de estudios y nivel de comprensión lectora en estudiantes del segundo grado de primaria en el Colegio Cooperativo César Vallejo, Iquitos 2022 - Zegarra Lanza, Daisi Oneida (2023)
Objective: The aim of this study was to determine the relation between the study habits and the reading comprehension levels in the in students of the second grade of elementary school of the Colegio Cooperativo César Vallejo, en Iquitos city, 2022. Materials and methods: It was applied two questionnaires to 119 childrens, previous validation for experts. The study was descriptive – relational and the design was not experimental. It was observed that between the study habits and the reading comprehension levels exists a significant relation (X2 =20,420) with a significance p = 0 < 0,05. Conclusion: The Study habits determine reading comprehension levels.